"Dear Future President of the United States": Analyzing Youth Civic Writing Within the 2016 Letters to the Next President Project. (June 2020) - Garcia, Antero; Levinson, Amber Maria; Gargroetzi, Emma Carene
This article investigates the civic writing practices of more than 11, 000 students writing letters to the next president in the lead up to the 2016 U.S. election. We analyze how letter topics are associated with socioeconomic factors and reveal that 43 topics—including ones prevalent among students such as immigration, guns, and school costs—were significantly associated with socioeconomic and racial majority indicators. Furthermore, we conducted a qualitative analysis of the kinds of arguments and evidence developed in letters from five schools serving predominantly lower income students and/or students of color in different regions of the country. Student arguments and types of evidence used were site dependent, suggesting the importance of teacher instruction. This analysis expands previous conceptions of youth civic learning.